2000
DOI: 10.4050/jahs.45.157
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Tip-Vortices in the Wake of a Two-Bladed Rotor in Axial Flight

Abstract: Roliil Jain'A. T. Conlisk Grad~tote Srrtrle,rr Prqfesuor Del~ort,nent of Mecl8onical E,~gbzeerblg, Tlte Ollio State Urrivemir)~In recent experiments, it was observed that the tip vortices shed from a two-bladed rotor can interact significantly. The interaction consists of a turn of the tip-vortex from one hlade rolling aronnd a turn of the tip-vortex from the other blade. Visualized in aplanarlightsheet, thetwo vorticesspiral aronnd each other prior to merging into asinglevortex. One complete cycle of the roll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…Landgrebe [1] and Tangler et al [2] both observed localized roll-up or 'pairing' of wake vortices, as did Martin et al [3] and Caradonna et al [4,5]. This has been confirmed by theoretical stability analyses [6][7][8], which imply a hovering rotor wake is fundamentally unstable with several unstable modes. Low diffusion numerical simulation methods, for example free-vortex or free-wake [8,9] or vorticity transport methods [10,11], have also shown evidence of unsteady wakes for rotors in hover, seemingly confirming both theoretical and experimental data.…”
Section: Introductionsupporting
confidence: 66%
“…Landgrebe [1] and Tangler et al [2] both observed localized roll-up or 'pairing' of wake vortices, as did Martin et al [3] and Caradonna et al [4,5]. This has been confirmed by theoretical stability analyses [6][7][8], which imply a hovering rotor wake is fundamentally unstable with several unstable modes. Low diffusion numerical simulation methods, for example free-vortex or free-wake [8,9] or vorticity transport methods [10,11], have also shown evidence of unsteady wakes for rotors in hover, seemingly confirming both theoretical and experimental data.…”
Section: Introductionsupporting
confidence: 66%
“…Experimental data for rotors in hover, for example, References [2][3][4][5], have suggested the wakes are actually unsteady. This has been confirmed by theoretical stability analyses [6][7][8], which imply a hovering rotor wake is fundamentally unstable with several unstable modes. Other simulation methods, for example, free-vortex or free-wake [8,9] or vorticity transport methods [10,11], with low inherent dissipation, have also shown evidence of unsteady hover wakes, confirming the theoretical and experimental data.…”
Section: Introductionsupporting
confidence: 59%
“…Recent experiments by Felli et al (2011) and Leweke et al (2013) as well as numerical studies by Widnall (1972) and Ivanell et al (2010) have confirmed that the mutual inductance instability leads to vortex pairing in the rotor wake, and they indicate that the vortex pairing is the primary cause of wake destabilization. The vortex pairing is a result of the vortex-induced velocities in a form that it is analogous to the leapfrogging motion of two inviscid vortex rings (Jain et al 1998). This phenomenon occurs in a row of equidistant identical vortices, whereby amplifications of small perturbations cause the vortices to oscillate in such a way that neighbouring vortices approach each other and start to group in pairs.…”
Section: Introductionmentioning
confidence: 99%